Effect Of Various Curing On High Strength Concrete Using Slag Cement - Rahmi Karolina; Handana, M.A.P; Jatmikanto, Rahmat (International Journal of Sustainable Construction Engineering and Technology, 2020)
A The current environmental problem is regarding to CO2 gas emissions from cement production and the presence of hazardous material waste (B3) from steel production. One solution for that problem is by applying slag cement as a substitute for type I portland cement in concrete mix to create a high quality concrete that is environmentally friendly with a high durability and initial strength. This research aimed to compare a high quality concrete made from slag cement and a high quality concrete with conventional mixture. The slag cement used was obtained from PT. Indocement Indonesia. It is coupled with the use of Master Ease 3029 superplasticizer. The results showed that from the samples of concrete of 3, 7, 14, 28, 56 and 90 days of age, the maximum absorption value of normal concrete occurs at the age of 90 days with acid water curing of 1.57%. While the maximum absorption value of slag cement concrete occurs at the same age with acid water curing of 1.50%. The curing of normal concrete with water at 56 days of age has the largest compressive strength from all. It is also found that slag cement concrete has higher maximum compressive strength than that of normal concrete with acid water curing at 56 days of curing.